Creating experiences in the experience economy - Sundbo, Jon.; Darmer, Per, 1956- (Cheltenham, UK : Edward Elgar, 2008)
'Creating Experiences in the Experience Economy focuses on the creation of experience from a business perspective. In doing so, the book establishes a more solid foundation for making better and more complex analyses of experience creation, paving the way for the development of analytically based and innovative experiences in experience firms and institutions. The contributors emphasise that experience creation is not an easy task with a straightforward formula and examine how marketed experiences are constructed, developed and innovated.''Presenting diverse and innovative perspectives, the contributors discuss and present models for how experiences are designed, produced and distributed. With its cross-disciplinary approach to experience creation, this fascinating study will appeal to researchers and academics of business administration, services, culture and tourism.'--Jacket.
Introduction to experience creation / Per Darmer, Jon Sundbo -- The food and eating experience / Jan Krag Jacobsen -- Designing innovative video games / Erik Kristiansen -- What makes Rome: ROME? A curious traveller's multisensory analysis of aspects of complex Roman experiences / BjrnLaursen -- The backstaging of experience production / Jon Sundbo, Peter Hagedorn-Rasmussen -- Entrepreneurs in music: the passion of experience creation / Per Darmer -- The urban innovation network geography of leisure experiences / Flemming S{u296E}sen -- Experience offerings: who or what does the action? / Connie Svabo -- Performing cultural attractions / Jn Ole B{u296E}holdt, Michael Haldrup, Jonas Larsen -- On sense and sensibility in performative processes / Henriette Christrup -- Experience production by family tourism providers / Ann Hartl, Malene Gram.
Includes bibliographical references and index.
Keywords: Marketing -- Psychological aspects; Experience -- Economic aspects; New products; Consumer behavior